1967
DOI: 10.1085/jgp.50.6.85
|View full text |Cite
|
Sign up to set email alerts
|

Myosin

Abstract: There is fairly general agreement that myosin isolated from rabbit skeletal muscle has a molecular weight of about 500,000. The higher values that have been reported apparently reflect protein aggregation related to the method of preparation. On the basis of present evidence, the myosin molecule has an elongate helical core of two f subunits (average weight about 215,000) that extend into a globular head region containing three g subunits (average weight about 20,000). Myosin may be dissociated into subunits b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
1

Year Published

1969
1969
1981
1981

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 76 publications
5
22
1
Order By: Relevance
“…k 5000, respectively. These values are in agreement with present estimates of the subunit sizes of the muscle proteins [37,38].…”
Section: Aggregation Of Hepatocyte Myosinsupporting
confidence: 92%
“…k 5000, respectively. These values are in agreement with present estimates of the subunit sizes of the muscle proteins [37,38].…”
Section: Aggregation Of Hepatocyte Myosinsupporting
confidence: 92%
“…In previous ultracentrifugal studies on rabbit skeletal myosin, we have reported that the light chains have a weight average tool wt of 20,000 and comprise approximately 12 ~ of the total myosin, the intact molecule having a mol wt of 470,000 (Gershman et al, 1966(Gershman et al, , 1969Dreizen et al, 1967). This evidence would imply the presence of three light chains (on the average) per myosin molecule.…”
Section: Considerations Of Structure-functlon Relationships In Myosinmentioning
confidence: 90%
“…In general those denaturing conditions which result in complete dissociation of light chains from myosin also lead to irreversible inactivation of myosin ATPase. For example, myosin ATPase is irreversibly denatured on alkaline treatment above pH 10, over the same range of pH where light chains are dissociated from myosin (Gershman et al, 1966(Gershman et al, , 1969Dreizen et al, 1967). A close relationship between subunit dissociation and irreversible loss of ATPase has also been found in a series of experiments on myosin in concentrated salt solutions at pH 7 and 4~ (Gershman et al, 1968;Dreizen and Gershman, 1970).…”
mentioning
confidence: 95%
See 2 more Smart Citations